Dispute resolution mechanisms in the Islamic finance industry in Malaysia: towards a legal framework - Engku Ali, Engku Rabiah Adawiah; Oseni, Umar Aimhanosi; Adewale, Abideen Adeyemi; Mohd. Zain, Nor Razinah (IIUM, 2015)
The recent ground breaking reforms in the legal and regulatory framework for Islamic banking and finance in Malaysia usher in a new phase in the modern history of this hitherto niche market. As part of these latest reforms, a major paradigm shift in the process of dispute resolution is the introduction of the financial ombudsman scheme (FOS) that typifies the classical muḥtasib model in Islamic law. Against this backdrop, this paper provides a theoretical framework of dispute resolution mechanisms in the Islamic banking and finance industry in Malaysia with special reference to the Islamic legal paradigm. While adopting an analytical approach in examining the relevant issues, the paper argues that effective dispute resolution mechanisms that are annexed to the traditional litigation process based on the Islamic legal paradigm will enhance the grievance redress system. It therefore proposes an Islamic-based multi-tier process of dispute resolution that does not only take into consideration the classical processes of dispute resolution in Islamic law but also their potentials in streamlining the prevailing dispute resolution framework in the Islamic banking and finance industry in Malaysia.